Prediction of rupture sites in abdominal aortic aneurysms after finite element analysis: $hPhilipp Erhart, MD, Joy Roy, MD, Jean-Paul P.M. de Vries, MD, PhD, Moritz Lindquist Liljeqvist, Caspar Grond-Ginsbach, PhD, Alexander Hyhlik-Dürr, MD, PhD, and Dittmar Böckler, MD, PhD - Erhart, Philipp; Roy, Joy; Vries, Jean-Paul P. M. de; Liljeqvist, Moritz Lindquist; Grond-Ginsbach, Caspar; Hyhlik-Dürr, Alexander; Böckler, Dittmar (Journal of endovascular therapy, 2016)
Purpose: To associate regions of highest local rupture risk from finite element analysis (FEA) to subsequent rupture sites in abdominal aortic aneurysms (AAA). ...
First published October 23, 2015
Gesehen am 08.05.2020